The Symptoms of Risk of Violence Behavior Decline after Given Prgressive Muscle Relaxation Therapy on Schizophrenia Patients - Jek Amidos Pardede; Galvani Volta Simanjuntak; Rutkotae Laia (Jurnal Ilmu Keperawatan Jiwa, 2020)
The Risk of violent behavior is a symptom of schizophrenia patients that can be controlled through progressive muscle relaxation therapy (PMRT). PMRT is a relaxation technique that focuses on muscle activity by identifying tense muscles and then reducing tension by doing relaxation techniques to get a feeling of relaxation. The purpose of this study was to determine the effect of PMRT on changes in symptoms of risk of violent behavior in schizophrenic patients, especially on the risk of violent behavior. This study uses a quasi-experimental pre-post test design. The population in this study amounted to 27 people with a total sample of 18 people. The sampling technique in this study was purposive sampling. The research instrument used was a questionnaire that had been tested for validity and reliability. Data were analyzed by Paired t-test with P-value = 0,000 <p = 0.05. The results showed that there was an effect of PMRT on changes in risk symptoms of violent behavior before and after PMRT. The conclusion that PMRT has a significant influence on changes in risk symptoms of violent behavior in RSJ Prof. Dr. M. Ildrem Provsu Medan.